2002
DOI: 10.1007/s00421-002-0582-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fatigue on spontaneous velocity variations in human middle-distance running: use of short-term Fourier transformation

Abstract: Best performances in middle-distance running are characterized by coefficients of variation of the velocity ranging from 1% to 5%. This seems to suggest that running at constant velocity is a strain inducing an increase in physiological variables such as oxygen uptake. This study tested three questions. (l) Does velocity variability during a middle-distance all-out run increase with fatigue? (2) Does velocity variability alter the slow phase of the oxygen kinetic because of small spontaneous recoveries, compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…It is well known, however, that VO 2 max is lower in cycling compared with a running exercise [6] and that the energy cost of running on a treadmill is not similar to running on a track [7,8]. Since this study was performed 10 years ago [5], technological progresses have made it possible to measure all the factors in field experiments by using breath-by-breath portable oxygen analyzers [8][9][10][11][12][13]. Elite athletes, who generally are not available for testing in laboratory conditions, are often more open to field tests.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known, however, that VO 2 max is lower in cycling compared with a running exercise [6] and that the energy cost of running on a treadmill is not similar to running on a track [7,8]. Since this study was performed 10 years ago [5], technological progresses have made it possible to measure all the factors in field experiments by using breath-by-breath portable oxygen analyzers [8][9][10][11][12][13]. Elite athletes, who generally are not available for testing in laboratory conditions, are often more open to field tests.…”
Section: Introductionmentioning
confidence: 99%
“…They used Fast Fourier transform to analyze the run speed and the physiological response ( and heart rate) variations. That study [3] suggested that an athlete might unconsciously modify his velocity to maintain a physiological steady state. In all subjects, no apparent systematization in running-speed changes was reported.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the adaptations of the autonomic nervous system activity has been widely studied through heart rate variability with Fourier transform to appreciate the autonomic control of heart rate variability during and after exercise [31][32][33]. Only one study [3] addressed spontaneous velocity changes with fatigue in all-out runs over the distance limit (dlim) at free spontaneous velocity or the same average, but constant, velocity (the minimal velocity that elicits max in an incremental test (v max ). They used Fast Fourier transform to analyze the run speed and the physiological response ( and heart rate) variations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations